2012
DOI: 10.4103/2249-4847.101705
|View full text |Cite
|
Sign up to set email alerts
|

Potter′s sequence

Abstract: Potter's sequence is a rare fatal disorder that occurs in sporadic and autosomal recessive forms with an incidence of 1 in 4000 births. Babies born with this condition are either still born or die very early within the neonatal period. We report a case of Potter's sequence with the typical physical findings and histological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 10 publications
1
24
0
2
Order By: Relevance
“…PS is also known as Potter's sequence, because, despite differences in the urological abnormalities in individual cases, the endpoint is always a severe decrease or absence of amniotic fluid [2]. PS is an unusual fatal disorder that predominantly affects male babies and is common in primigravid mothers [2,3]. PS has been divided into four distinct subgroups (Table 1) [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PS is also known as Potter's sequence, because, despite differences in the urological abnormalities in individual cases, the endpoint is always a severe decrease or absence of amniotic fluid [2]. PS is an unusual fatal disorder that predominantly affects male babies and is common in primigravid mothers [2,3]. PS has been divided into four distinct subgroups (Table 1) [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The sequence is associated with bilateral renal agenesis, oligohydramnios, and pulmonary hypoplasia (PH). Renal abnormalities, which can include bilateral renal agenesis, severe hypoplasia, dysplasia, polycystic kidney, or obstructive uropathy, are the primary defect [1][2][3]. The incidence of PS in multiple pregnancies remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there has been a decline in the rate of autopsy worldwide for decades, a fact that has been widely documented [27][28][29][30][31][32][33][34][35]. Studies have shown that the declining rate of non-coroner autopsies is caused by the creation of bioethics laws [36], patients views on the practice which makes it difficult to obtain consent from relatives; advances in modern diagnostic techniques [37,38], delay in obtaining autopsy reports [39], concerns about disfigurement and other cultural [40,41] or religious reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual autopsy PME by multi-slice computed tomography (MSCT) and magnetic resonance imaging (MRI) [29], is an innovative technique in forensic medicine that may be used as a part of PME [21] or as an alternative tool to the classic forensic autopsy. However, its use as an alternative to autopsy is yet in its nascent phases [30] although several institutions worldwide have implemented it in their medico-legal workflow [22].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, bilateral renal agenesis (BRA) leads to a rare fatal disorder known as Potter sequence, which affects 1:4000 live births [98,110]. This disease is characterized by facial, limb and pulmonary malformations secondary to a lack of urine-derived amniotic fluid, which causes respiratory failure and premature death [98].…”
Section: Pax Genes and Cakutmentioning
confidence: 99%